Waste gypsum-based polymer and preparation method thereof
By using materials such as calcined desulfurized gypsum and steel slag micron powder, and preparing a multi-functional setting regulator, the problem of unstable setting time of waste gypsum-based polymer concrete was solved, achieving good construction performance and mechanical properties, and significantly increasing the value of the material. .
Patent Information
- Application Number
- CN202411507025.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-10-28
AI Technical Summary
In the prior art, the settling time of the waste gypsum base polymer concrete is difficult to control, resulting in insufficient strength development and cracks, and the coagulant used may have environmental pollution and stability problems.
Calcined desulfurized gypsum is used as the main component, combined with steel slag powder and mineral powder, and a coagulant with multi-functional groups is prepared to adjust the coagulation time of the geopolymer and cooperate with the water-reducing agent to adjust the flow properties of the mixture slurry.
The prepared waste gypsum-based polymer has good construction performance, mechanical properties and crack resistance, which greatly increases the value of industrial by-products.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of geopolymer-based building materials, in particular to a waste gypsum-based polymer and a preparation method thereof. Background Art
[0002] Globally, the massive accumulation of industrial by-products such as waste gypsum, especially desulfurized gypsum, poses a serious challenge to the environment.
[0003] At the same time, the construction industry's demand for high-performance, environmentally friendly concrete continues to grow.
[0004] As an innovative material, waste gypsum-based polymer concrete has shown great application potential by effectively utilizing waste gypsum.
[0005] Waste gypsum-based polymer concrete is a new type of cementitious material that uses industrial waste gypsum as the main raw material and is activated by a geopolymer chemical activator. Compared with traditional concrete, it has lower energy consumption, less carbon dioxide emissions, and good mechanical properties and durability. However, its setting time is difficult to control, which may lead to insufficient strength development and the formation of cracks. Therefore, in the preparation process of waste gypsum-based polymer concrete, it is urgently necessary to develop corresponding setting regulators.
[0006] Reference 1 (Lv Xingdong, Wang Xuebin, Li Beixing. Application of organic phosphonic acid compounds in concrete engineering and research progress on retarding mechanism [J]. Materials Guide, 2020, 34(08): 15184-15189.) published a method of using organic phosphonic acid compounds as setting regulators.
[0007] The method reduces temperature cracks in concrete by adding organic phosphonic acid compounds with hydration heat inhibition effect to reduce the hydration heat release and heat release rate of the cementitious system.
[0008] Reference 2 (Zhang Jie, Zhang Jingxuan, Rong Shuoshuo, Application of polycarboxylic acid water reducer and compound retarder in sleeper concrete [J], Value Engineering, 2024 (19): 128-130) discloses a method of using polycarboxylic acid water reducer as a concrete retarder.
[0009] The method uses polycarboxylate water reducer to reduce the amount of water and cement, thereby reducing the initial defects of concrete caused by creep, shrinkage, cement hydration heat, etc.
[0010] Reference 3 (Feng Yuqiang. Research on the influence of retarders on concrete properties [J]. New Materials and New Decoration, 2023, 05(08):13-15) uses sucrose and sodium gluconate as retarders to test their effects on concrete properties. The results show that a certain amount of retarder is beneficial to the strength growth of concrete at all ages, and the combined effect of the compound is more beneficial to the strength of concrete.
[0011] The shortcomings of the above technology are:
[0012] (1) Reference 1 uses organic phosphonic acid compounds. The production and use of organic phosphonic acid compounds may cause environmental pollution and may have long-term impacts on the ecosystem. Wastewater containing organic phosphonic acid compounds is also difficult to treat. Some organic phosphonic acid compounds are relatively stable to light, heat, and oxygen, but are easily decomposed by alkali, which may limit their stability and effectiveness in certain applications.
[0013] (2) Reference 2 uses polycarboxylate water-reducing agent, which may not be able to effectively maintain the slump of concrete under high temperature conditions, thus affecting construction.
[0014] Carboxylic acid water reducer is sensitive to temperature changes, and the slump resistance of concrete may vary greatly during construction in different seasons.
[0015] Currently, there are relatively few functional products of polycarboxylic acid water reducers on the market, which may be difficult to meet special construction requirements, and the raw material cost of polycarboxylic acid water reducers is relatively high.
[0016] (3) Although sodium gluconate in Reference 3 can also act as a retarder, its retarding effect increases with the increase of the dosage. There is a critical dosage. After exceeding this critical point, the final setting time increases rapidly, which may cause the concrete to set too long during construction.
[0017] The addition of sucrose promotes a significant increase in the calcium ion concentration in the solution, which remains in a supersaturated state for a long time and may affect the hydration balance of cement. Summary of the invention
[0018] In order to solve the problems existing in the prior art, the present invention provides a waste gypsum-based polymer. Specifically, desulfurized gypsum is used as waste gypsum for research and development, and steel slag powder and mineral powder are added as active raw materials after calcination, and a dedicated setting agent is prepared to regulate the setting time of the geopolymer, so as to prepare a waste gypsum-based polymer with good construction performance, mechanical properties and crack resistance, thereby greatly improving the value of industrial by-products.
[0019] Specifically, the waste gypsum-based polymer of the present invention is composed of the following raw materials in parts by weight:
[0020] Calcined desulfurized gypsum 50-60 parts, steel slag powder 15-20 parts, mineral powder 25-30 parts, setting agent 10-13 parts, water reducer 2-2.5 parts, water 25-30 parts,
[0021] Preferably, the calcined desulfurized gypsum is obtained by treating desulfurized gypsum at 130-150°C.
[0022] Preferably, the preparation process of the setting agent is:
[0023] a. Mix cotton fiber and bagasse in a mass ratio of (1-1.5): 1, add sodium hydroxide solution for alkalization, squeeze and remove water to obtain material A.
[0024] b. Add material A, propylene oxide, methyl chloride, dinitrobenzoic acid, chlorosulfonic acid, isopropanol and water in a mass ratio of 1:(0.8-1.2):(0.3-0.5):(0.3-0.4):(0.2-0.4):(4-5):(1-2) into a reactor and react at a pressure of 1.7-1.8 MPa and a temperature of 60-80°C to obtain material B.
[0025] c. Wash material B with oxalic acid solution, dry, and crush to obtain material C.
[0026] d. Mix material C, co-solvent, stabilizer and water in a mass ratio of 1:(20-25):(3-5):(90-100) to obtain the product.
[0027] Desulfurized gypsum is derived from the flue gas desulfurization process of coal-fired power plants, and its main component is calcium sulfate dihydrate. The present invention uses it as the main component to prepare geopolymer after calcination. During the experiment, it was found that the main component of the desulfurized gypsum after calcination is hemihydrate gypsum, which has a fast setting speed and contains some impurities, which affects the setting time and mechanical properties of the geopolymer. The present invention prepares a setting regulator with multi-functional groups for calcined desulfurized gypsum to adjust its setting time, and cooperates with a water reducer to adjust the flow properties of the mixture slurry.
[0028] Preferably, the moisture content of material A in step a is ≤3%.
[0029] Preferably, the mass concentration of the oxalic acid solution in step c is 15-17%, and the temperature is 70-80°C.
[0030] Preferably, a universal grinder is used for pulverizing in step c.
[0031] Preferably, the particle size of material C in step c is ≤50 μm.
[0032] Preferably, the cosolvent in step d is propylene glycol.
[0033] Preferably, the stabilizer in step d is N-n-alkylbenzisothiazolone.
[0034] Preferably, the water reducer is a polycarboxylate water reducer.
[0035] The present invention adopts calcined desulfurized gypsum as the main material. The main component of the calcined desulfurized gypsum is β-semihydrate gypsum, which has coagulation and hardening properties. The hydration of the semihydrated gypsum forms calcium sulfate, which can be used as a sulfate activator to activate steel slag powder and mineral powder to form hydraulic hydration products, thereby improving the mechanical properties of the geopolymer.
[0036] The present invention also relates to a method for preparing the above waste gypsum-based polymer, which specifically comprises the following steps:
[0037] (1) Weigh each raw material by weight.
[0038] (2) Mix the calcined desulfurized gypsum, steel slag powder and mineral powder evenly, add setting agent, water reducing agent and water, mix evenly to obtain a mixture slurry.
[0039] (3) The mixed slurry is formed and cured.
[0040] Preferably, the curing in step (3) adopts standard curing.
[0041] The present invention has the following technical advantages:
[0042] 1. The setting regulator prepared by the present invention has a good retarding effect on the desulfurized gypsum-based polymer, is easy to store, and has high purity.
[0043] 2. The present invention uses calcined desulfurized gypsum, steel slag powder and mineral powder as cementitious materials to realize resource utilization of industrial solid waste.
[0044] 3. The preparation process of the present invention is simple, the geopolymer has good construction performance and mechanical properties, and excellent anti-cracking effect. DETAILED DESCRIPTION
[0045] In order to characterize the technical effect of the present invention, geopolymers were prepared and their properties were tested.
[0046] The calcined desulfurized gypsum is obtained by calcining desulfurized gypsum at 150°C for 1.5 hours, the water reducer adopts polycarboxylic acid water reducer with a water reduction rate of 24%, the co-solvent is propylene glycol, and the stabilizer is N-alkylbenzisothiazolone.
[0047] Example 1
[0048] Geopolymer is composed of the following raw materials in parts by weight: 56 parts of calcined desulfurized gypsum, 18 parts of steel slag powder, 26 parts of mineral powder, 11 parts of setting agent, 2.2 parts of water reducer, and 28 parts of water.
[0049] The preparation process of the coagulant is as follows:
[0050] a. Mix cotton fiber and bagasse in a mass ratio of 1.2:1, add sodium hydroxide solution for alkalization, squeeze and remove water to obtain material A.
[0051] b. Add material A, propylene oxide, methyl chloride, dinitrobenzoic acid, chlorosulfonic acid, isopropanol and water into the reactor in a mass ratio of 1:1.2:0.4:0.4:0.3:4.2:2, and react at a pressure of 1.7 MPa and a temperature of 70°C to obtain material B.
[0052] c. Wash material B with oxalic acid solution, dry, and crush to obtain material C.
[0053] d. Mix material C, co-solvent, stabilizer and water in a mass ratio of 1:23:4:100 to obtain the product.
[0054] After testing, the initial fluidity of the mixture slurry is 230mm, the workability is good, the initial setting time is 6h25min, the final setting time is 10h30min, the 28d compressive strength is 43.6MPa, the 28d flexural strength is 3.6MPa, and there are no cracks on the surface of the specimen after magnified observation.
[0055] Example 2
[0056] Geopolymer is composed of the following raw materials in parts by weight: 60 parts of calcined desulfurized gypsum, 15 parts of steel slag powder, 30 parts of mineral powder, 12 parts of setting agent, 2.3 parts of water reducer, and 28 parts of water.
[0057] The preparation process of the coagulant is as follows:
[0058] a. Mix cotton fiber and bagasse in a mass ratio of 1.5:1, add sodium hydroxide solution for alkalization, squeeze and remove water to obtain material A.
[0059] b. Add material A, propylene oxide, methyl chloride, dinitrobenzoic acid, chlorosulfonic acid, isopropanol and water into the reactor in a mass ratio of 1:1:0.4:0.3:0.4:4:2, and react at a pressure of 1.7 MPa and a temperature of 70°C to obtain material B.
[0060] c. Wash material B with oxalic acid solution, dry, and crush to obtain material C.
[0061] d. Mix material C, co-solvent, stabilizer and water in a mass ratio of 1:20:4:95 to obtain the product.
[0062] After testing, the initial fluidity of the mixture slurry is 220mm, the workability is good, the initial setting time is 6h40min, the final setting time is 10h15min, the 28d compressive strength is 45.3MPa, the 28d flexural strength is 3.9MPa, and there are no cracks on the surface of the specimen after magnified observation.
[0063] Comparative Example 1
[0064] The geopolymer is composed of the following raw materials in parts by weight: 56 parts of calcined desulfurized gypsum, 18 parts of steel slag powder, 26 parts of mineral powder, 2 parts of sodium gluconate, 2.2 parts of water reducer and 35 parts of water.
[0065] After testing, the initial fluidity of the mixture slurry was 190mm, the slurry exuded, the initial setting time was 1h15min, the final setting time was 2h, the 28d compressive strength was 34.7MPa, the 28d flexural strength was 2.6MPa, and a small amount of microcracks were found on the surface of the specimen after magnified observation.
[0066] Comparative Example 2
[0067] Geopolymer is composed of the following raw materials in parts by weight: 56 parts of calcined desulfurized gypsum, 18 parts of steel slag powder, 26 parts of mineral powder, 11 parts of setting agent, 2.2 parts of water reducer, and 28 parts of water.
[0068] The preparation process of the coagulant is as follows:
[0069] a. Add sodium hydroxide solution to the sugarcane bagasse for alkalization treatment, squeeze and remove water to obtain material A.
[0070] b. Add material A, propylene oxide, methyl chloride, dinitrobenzoic acid, chlorosulfonic acid, isopropanol and water into the reactor in a mass ratio of 1:1.2:0.4:0.4:0.3:4.2:2, and react at a pressure of 1.7 MPa and a temperature of 70°C to obtain material B.
[0071] c. Wash material B with oxalic acid solution, dry, and crush to obtain material C.
[0072] d. Mix material C, co-solvent, stabilizer and water in a mass ratio of 1:23:4:100 to obtain the product.
[0073] After testing, the initial fluidity of the mixture slurry was 210mm, and compaction occurred. The initial setting time was 5h5min, the final setting time was 9h30min, the 28d compressive strength was 40.5MPa, the 28d flexural strength was 3.2MPa, and there were no cracks on the surface of the specimen after magnified observation.
[0074] Comparative Example 3
[0075] Geopolymer is composed of the following raw materials in parts by weight: 56 parts of calcined desulfurized gypsum, 18 parts of steel slag powder, 26 parts of mineral powder, 11 parts of setting agent, 2.2 parts of water reducer, and 28 parts of water.
[0076] The preparation process of the coagulant is as follows:
[0077] a. Mix cotton fiber and bagasse in a mass ratio of 1.2:1, add sodium hydroxide solution for alkalization, squeeze and remove water to obtain material A.
[0078] b. Add material A, propylene oxide, methyl chloride, isopropanol and water in a mass ratio of 1:1.2:1.1:4.2:2 into the reactor and react at a pressure of 1.7 MPa and a temperature of 70°C to obtain material B.
[0079] c. Wash material B with oxalic acid solution, dry, and crush to obtain material C.
[0080] d. Mix material C, co-solvent, stabilizer and water in a mass ratio of 1:23:4:100 to obtain the product.
[0081] After testing, the initial fluidity of the mixture slurry was 190mm, and compaction occurred. The initial setting time was 3h50min, the final setting time was 8h, the 28d compressive strength was 36.9MPa, the 28d flexural strength was 2.8MPa, and there were no cracks on the surface of the specimen after magnified observation.
[0082] Comparative Example 4
[0083] Geopolymer is composed of the following raw materials in parts by weight: 56 parts of calcined desulfurized gypsum, 18 parts of steel slag powder, 26 parts of mineral powder, 11 parts of setting agent, 2.2 parts of water reducer, and 28 parts of water.
[0084] The preparation process of the coagulant is as follows:
[0085] a. Mix cotton fiber and bagasse in a mass ratio of 1.2:1, add sodium hydroxide solution for alkalization, squeeze and remove water to obtain material A.
[0086] b. Add material A, propylene oxide, methyl chloride, chlorosulfonic acid, isopropanol and water in a mass ratio of 1:1.2:0.6:0.5:4.2:2 into the reactor and react at a pressure of 1.7 MPa and a temperature of 70°C to obtain material B.
[0087] c. Wash material B with oxalic acid solution, dry, and crush to obtain material C.
[0088] d. Mix material C, co-solvent, stabilizer and water in a mass ratio of 1:23:4:100 to obtain the product.
[0089] After testing, the initial fluidity of the mixture slurry was 200mm, slightly compacted, the initial setting time was 7h10min, the final setting time was 9h45min, the 28d compressive strength was 38.7MPa, the 28d flexural strength was 2.7MPa, and there were no cracks on the surface of the specimen after magnified observation.
[0090] Comparative Example 5
[0091] The geopolymer is composed of the following raw materials in parts by weight: 20 parts of desulfurized gypsum, 28 parts of fly ash, 46 parts of mineral powder, 10 parts of water glass, 2 parts of sodium gluconate, 2.2 parts of water reducing agent and 30 parts of water.
[0092] After testing, the initial fluidity of the mixture slurry was 240mm, the initial setting time was 1h20min, the final setting time was 2h20min, the 28d compressive strength was 38.4MPa, the 28d flexural strength was 3.1MPa, and microcracks were found on the surface of the specimen after magnified observation.
[0093] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A waste gypsum-based polymer, characterized in that: It is composed of the following raw materials in parts by weight: Calcined desulfurized gypsum 50-60 parts, steel slag powder 15-20 parts, mineral powder 25-30 parts, setting agent 10-13 parts, water reducer 2-2.5 parts, water 25-30 parts, The calcined desulfurized gypsum is obtained by treating the desulfurized gypsum at 130-150°C. The preparation process of the setting agent is as follows: a. Mix cotton fiber and bagasse in a mass ratio of (1-1.5): 1, add sodium hydroxide solution for alkalization, squeeze and remove water to obtain material A. b. Add material A, propylene oxide, methyl chloride, dinitrobenzoic acid, chlorosulfonic acid, isopropanol and water in a mass ratio of 1:(0.8-1.2):(0.3-0.5):(0.3-0.4):(0.2-0.4):(4-5):(1-2) into a reactor and react at a pressure of 1.7-1.8 MPa and a temperature of 60-80°C to obtain material B. c. Wash material B with oxalic acid solution, dry, and crush to obtain material C. d. Mix material C, co-solvent, stabilizer and water in a mass ratio of 1:(20-25):(3-5):(90-100) to obtain the product.
2. The waste gypsum-based polymer according to claim 1, characterized in that: The moisture content of material A in step a is ≤3%.
3. The waste gypsum-based polymer according to claim 1, characterized in that: In step c, the mass concentration of the oxalic acid solution is 15-17% and the temperature is 70-80°C.
4. The waste gypsum-based polymer according to claim 1, characterized in that: In step c, a universal grinder is used for crushing.
5. The waste gypsum-based polymer according to claim 1, characterized in that: The particle size of material C in step c is ≤50 μm.
6. The waste gypsum-based polymer according to claim 1, characterized in that: In step d, the cosolvent is propylene glycol.
7. The waste gypsum-based polymer according to claim 1, characterized in that: In step d, the stabilizer is N-n-alkylbenzisothiazolone.
8. The waste gypsum-based polymer according to claim 1, characterized in that: The water reducer is a polycarboxylate water reducer.
9. The method for preparing a waste gypsum-based polymer according to any one of claims 1 to 8, characterized in that: The steps include: (1) Weigh each raw material by weight. (2) Mix the calcined desulfurized gypsum, steel slag powder and mineral powder evenly, add setting agent, water reducing agent and water, mix evenly to obtain a mixture slurry. (3) The mixed slurry is formed and cured.
10. The preparation method according to claim 9, characterized in that: The maintenance in step (3) adopts standard maintenance.
Citation Information
Patent Citations
Method for preparing carboxymethyl cellulose (CMC) and lignin from bagasse
CN102108099A
Environment-friendly cement-based material for pavement base
CN105418046A